UMTS Radio Network Planning: Mastering Cell Coupling for Capacity Optimization - Geerdes, Hans-Florian.; SpringerLink (Online service) (Wiesbaden : Vieweg+Teubner, 2008)
Interference determines the performance of UMTS radio networks. In order to provide good coverage and high capacity, network operators need to control the effects and dynamics of interference coupling among users and cells. This is a major challenge in planning and optimizing UMTS radio networks. Hans-Florian Geerdes establishes a concise system model, which describes interference coupling and its impact on the network. The system model enables an efficient analysis of radio network performance. It is also the basis for new automatic planning algorithms. Extensive computational experiments on realistic data demonstrate that the presented evaluation and optimization methods are well-suited tools for use in practice.
Radio network modeling and performance evaluation for UMTS -- Interference-coupling complementarity systems -- Expected-interference-coupling estimates for network performance -- Network performance optimization -- Conclusion.
Keywords: Computer science; Computer communication systems; Electrical engineering; Computer Science; Computer Communication Networks; Communications Engineering, Networks; Computer Science, general; Electronic books